Articulating Qur’anic Values in Javanese Cosmology: A Hermeneutical Reading of Kawruh Jiwa of Ki Ageng Suryomentaram - Safei, Abdullah; Muhammad Irawan Taqwa; Agus Handoko; Zakaria Abdiwali Muhammed (KALAM, 2026)
This study argues that Ki Ageng Suryomentaram’s (KAS) Kawruh Jiwa is not merely an indigenous psychological framework but a sophisticated vernacularization of Qur’anic values within Javanese intellectualism. While previous scholarship focuses on its psychological dimensions, this research positions Kawruh Jiwa as a dialectical product between divine revelation and local cosmology. Employing a qualitative method rooted in Gadamerian philosophical hermeneutics—specifically the concept of "fusion of horizons"—this research analyzes KAS’s key texts to uncover their theological intersections with Qur’anic concepts. The findings demonstrate that KAS’s teachings reconfigure Tazkiyatun Nafs (purification of the soul) through local wisdom: Kramadangsa serves as a manifestation of Nafs al-Ammarah, while Mawas Diri functions as a contextualized practice of Muhasabah. This study concludes that Suryomentaram’s work acts as a "cultural exegesis" that integrates Javanese identity with Qur’anic spirituality. These findings offer a theoretical contribution to the study of Islam Nusantara by providing a hermeneutical model on how universal religious values can be indigenized without losing their theological essence. [Penelitian ini berargumen bahwa ajaran Kawruh Jiwa Ki Ageng Suryomentaram (KAS) bukan sekadar kerangka psikologi pribumi, melainkan sebuah vernakularisasi nilai-nilai Al-Qur'an yang canggih dalam intelektualisme Jawa. Jika penelitian sebelumnya cenderung berfokus pada dimensi psikologis, riset ini memposisikan Kawruh Jiwa sebagai produk dialektis antara wahyu ilahi dan kosmologi lokal. Dengan menggunakan metode kualitatif yang berakar pada hermeneutika filosofis Gadamerian—khususnya konsep "peleburan cakrawala" (fusion of horizons)—penelitian ini menganalisis teks-teks utama KAS untuk mengungkap titik temu teologisnya dengan konsep-konsep Al-Qur'an. Temuan penelitian menunjukkan bahwa ajaran KAS mengonfigurasi ulang konsep Tazkiyatun Nafs (penyucian jiwa) melalui kearifan lokal: Kramadangsa diidentifikasi sebagai manifestasi dari Nafs al-Ammarah, sementara Mawas Diri berfungsi sebagai praktik Muhasabah yang terkontekstualisasi. Penelitian ini menyimpulkan bahwa karya Suryomentaram berfungsi sebagai "eksegesis budaya" yang mengintegrasikan identitas Jawa dengan spiritualitas Al-Qur'an. Temuan ini memberikan kontribusi teoretis bagi studi Islam Nusantara dengan menyediakan model hermeneutis tentang bagaimana nilai-nilai agama universal dapat dipribumikan tanpa kehilangan esensi teologisnya.]